2009
DOI: 10.1093/mp/ssn085
|View full text |Cite
|
Sign up to set email alerts
|

HOS3, an ELO-Like Gene, Inhibits Effects of ABA and Implicates a S-1-P/Ceramide Control System for Abiotic Stress Responses in Arabidopsis thaliana

Abstract: A hyper-osmotically sensitive mutant of Arabidopsis thaliana, designated hos3-1 (high expression of osmotically responsive genes), was identified based on its hyper-luminescence of RD29A:LUC promoter fusion plants upon treatment with NaCl and ABA. These responses implicate the disrupted gene as a direct or indirect negative regulator of the RD29A stress-responsive pathway. By sequencing the flanking regions of the T-DNA borders, it was determined that the disrupted gene is at locus At4g36830, annotated as enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 60 publications
(95 reference statements)
0
33
0
Order By: Relevance
“…Disruption of VLCFA production in the hos3 mutant causes ceramide deficiency and affects ABA-related stress responses, such as root growth inhibition, seed germination with ABA treatment and water loss from leaves. These results implicate HOS3 and VLCFA pathway products in several aspects of ABAmediated stress signaling (Quist et al, 2009).…”
Section: The Biosynthesis Of Vlcfasmentioning
confidence: 62%
“…Disruption of VLCFA production in the hos3 mutant causes ceramide deficiency and affects ABA-related stress responses, such as root growth inhibition, seed germination with ABA treatment and water loss from leaves. These results implicate HOS3 and VLCFA pathway products in several aspects of ABAmediated stress signaling (Quist et al, 2009).…”
Section: The Biosynthesis Of Vlcfasmentioning
confidence: 62%
“…There are two families of condensing enzymes in Arabidopsis (Arabidopsis thaliana). The ELONGATION-DEFECTIVE (ELO)-LIKE family is homologous to yeast (Saccharomyces cerevisiae) ELOs, and has putative functions in sphingolipid biosynthesis (Quist et al, 2009). Although our current understanding of plant ELO-LIKE physiological function and biochemical activity is limited, the mechanism of yeast Elo protein activity has been thoroughly investigated (Denic and Weissman, 2007).…”
mentioning
confidence: 99%
“…However, we found that AtELO4 exhibited predominantly high expression in roots and weaker expression in leaves. In addition, previous studies showed that loss of function mutants of AtELO4 resulted in decreased VLCFA in roots and affected root growth [8], suggesting that AtELO4 played an important role in roots. Therefore, more complete and accurate temporal and spatial expres sion data for AtELO family was presented in our study.…”
Section: Discussionmentioning
confidence: 93%
“…ELO [7]. AtELO4, one member of ELO like family was confirmed to comple ment yeast ELO2 and ELO3 mutants and reduced the expression of AtELO4 resulted in approximately 15% increase in C22:0 level, 20% increase in C24:0 level, and 35% decrease in C26:0 level in leaves of atelo4 mutants as compared with those in Arabidopsis wild type plants [8]. However, much information of ELO like family members on developmental expres sion pattern, subcellular localization, and fatty acid profiles in AtELO knock out/down mutants remains elusive.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation